Hydraulic Stope Filling on the Golden Mine (The Australasian Institute of Mining and Metallurgy, 1965)
G. R. Compton (Gold Mines of Kalgoorlie (Australia) Ltd., Fimiston, W. A.) : In congratulating Mr. Hooker upon his resume of Mr Parry's paper I have in mind the fact that he carried out the research into pipe pressures. Hydraulic filling as practised in Kalgoorlie has created world wide interest, with these pressures and percolation being vital points.Early in the 1950s, representatives of the Kolar field were conduGted over the local mines where stopes at depths below 2,000 ft were being filled. The problems of pipe pressures were their main consideration since depths of up to 10,000 ft were envisaged.Mr Krishnaiah and Mr Murthy from the same field are with us today and perhaps we may hear of their experiences with depths of 6,000 ft and long lateral lines.J. Holly (Lake View and Star Ltd., Fimiston, W.A.): There is one phase, which I would like to mention myself, that has been very evident in Kalgoorlie operations. That is, we do not get the percolation properties that are obtained on many other fields in the world, and our tendency here has been to assess the quality of our fill more by its settling rate, i.e. the rate at which we can draw off clear water at the surface of the filling levels, rather than the rate that this water percolates down through the fill before it consolidates.We are tending now to measure the quality of our fill as a settling rate rather than as a percolation rate.Americans talk about percolation rates being the important property: If anyone has any experience on operating with fills with different percolation rates, I think their views would be very interesting to the meeting art this stage. Mr ...